2018
DOI: 10.3847/1538-4357/aab70c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fallback Accretion on Protomagnetar Outflows in Gamma-Ray Bursts and Superluminous Supernovae

Abstract: Rapidly spinning, strongly magnetized proto-neutron stars ("millisecond proto-magnetars") are candidate central engines of long-duration gamma-ray bursts (GRB), superluminous supernovae (SLSNe), and binary neutron star mergers. Magnetar birth may be accompanied by the fall-back of stellar debris, lasting for seconds or longer following the explosion. Accretion alters the magnetar evolution by (1) providing an additional source of rotational energy (or a potential sink, if the propeller mechanism operates); (2)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 135 publications
1
136
0
Order By: Relevance
“…The initial magnetic field of the magnetars at birth can be constrained to the range B 0 = 3 × 10 14 − 10 15 G (see also Gullón et al 2015). This is consistent with magnetic field values that are required for millisecond magnetars to power superluminous supernovae (SLSNe; 5 https://swift.gsfc.nasa.gov/archive/grb_table/ Metzger et al 2015Metzger et al , 2018 and gamma-ray bursts (GRBs; Beniamini et al 2017;Metzger et al 2018). The other important ingredient for powering those energetic explosions is the initial spin of the magnetar, Ω 0 .…”
Section: Discussionsupporting
confidence: 64%
“…The initial magnetic field of the magnetars at birth can be constrained to the range B 0 = 3 × 10 14 − 10 15 G (see also Gullón et al 2015). This is consistent with magnetic field values that are required for millisecond magnetars to power superluminous supernovae (SLSNe; 5 https://swift.gsfc.nasa.gov/archive/grb_table/ Metzger et al 2015Metzger et al , 2018 and gamma-ray bursts (GRBs; Beniamini et al 2017;Metzger et al 2018). The other important ingredient for powering those energetic explosions is the initial spin of the magnetar, Ω 0 .…”
Section: Discussionsupporting
confidence: 64%
“…Since the deduced braking index n < 3, besides the magnetic dipole torque, another braking mechanism should play an important role. For instance, fall-back accretion onto the magnetar could lead to n < 3 (Metzger et al 2018). This braking index is not surprising as a systematic study of a large sample of GRBs (long and short) with X-ray plateaus also suggested n significantly smaller than 3 (Stratta et al 2018).…”
Section: Constraining the Stellar Propertiesmentioning
confidence: 90%
“…where Ω K = GM/R 3 1/2 ; (2) N dip is the magnetic dipole radiation torque for accreting NSs with r m < r lc , enhanced over the standard dipole torque by a factor of (r lc /r m ) 2 > 1 due to the enhanced open magnetic field lines via the compression of the magnetosphere (Parfrey et al 2016;Metzger et al 2018).…”
Section: α − ω Dynamomentioning
confidence: 99%